2015
DOI: 10.1016/j.jallcom.2014.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transfer in mixtures of ethylene glicol with carbon coated iron nanoparticles under the influence of a uniform magnetic field

Abstract: International audienceIn this work, the study of the heat transfer enhancement induced by aligning iron nanoparticles in an ethylenglicol fluid matrix is presented. In particular the effect of the interface is studied by analyzing the cases in which the nanoparticles are coated with carbon and comparing with uncoated ones. Results indicate that the coating acts as a thermal barrier making thermal conductivity to decrease. Moreover, the magnetic field creates aligned columns that enhance the heat transfer. Effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It seems carbon coated metal/alloy nanoparticles with core-shell structure have more advantages relatively. Carbon coatings can protect metal core in ambient conditions, maintaining excellent thermal properties, and offering an economically attractive route to broader use of metal nanoparticles [24,[27][28][29] . The granule shape in nanometer size can be more easily to spread and occupy a little space in the adsorbent, therefore should void causing greater obstruction of mass transfer.…”
Section: Introduction mentioning
confidence: 99%
“…It seems carbon coated metal/alloy nanoparticles with core-shell structure have more advantages relatively. Carbon coatings can protect metal core in ambient conditions, maintaining excellent thermal properties, and offering an economically attractive route to broader use of metal nanoparticles [24,[27][28][29] . The granule shape in nanometer size can be more easily to spread and occupy a little space in the adsorbent, therefore should void causing greater obstruction of mass transfer.…”
Section: Introduction mentioning
confidence: 99%
“…On the other hand, due to the presence of oleic acid capping on the surface, the Kapitza resistance of the surface-functionalized GNP nanoinclusions was expected to be higher, and based on the thermal conductivity model for coated nanospheres, 49 the value was estimated as ∼8 × 10 –8 m 2 K W –1 (Section S4, in the Supporting Information, describes the calculations in detail), which was then fitted into the model proposed by Chu et al. 53 to obtain the theoretical values of k / k m for the oleic acid-coated GNP nanoinclusions.…”
Section: Resultsmentioning
confidence: 99%
“…48 This is more evident in the solid state, where the thermal transport is primarily through the percolating network of the aggregates, which resulted in comparatively lower thermal conductivity enhancements for the PCM loaded with oleic acid-functionalized graphene nanoplatelets (GNPs). Vales-Pinzon et al 49 also reported an effective decrease in thermal conductivity of ethylene glycolbased nanofluid containing iron nanoparticles after surface capping with carbon. On the other hand, Li et al 50 reported an increase in the thermal conductivity of the water-based SiO 2coated graphene nanofluid, which was attributed to the increased hydrophilic interaction of silica-coated graphene, resulting in lower interfacial thermal resistance and larger stability in the aqueous medium.…”
Section: Acs Omegamentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with CNT, nanoparticles such as Carbon coated Nickel (Ni@C) with core-shell structure manifests the potentials for the improvement of the sorption kinetics. One remarkable fact is that carbon coating is able to protect the external conditions for the metal core, and the metal core may take promoting effects on the composites while maintaining its desirable thermal properties [20][21][22]. The granular shape in nanometer size tends to be easier to occupy the porous structure of the composite sorbent with ENG.…”
Section: Introductionmentioning
confidence: 99%